Energetic particle impact on X‐ray imaging with XMM‐Newton. Issue 6 (6th June 2014) - Walsh, B. M.; Kuntz, K. D.; Collier, M. R.; Sibeck, D. G.; Snowden, S. L.; Thomas, N. E.
Abstract Since energetic protons (∼100 keV) hinder space‐based X‐ray imaging, there is a need to characterize the proton environments encountered by a soft X‐ray mission when planning missions and operations in the near‐Earth environment. Impacts range from enhanced noise in the images to damage to CCD detectors. The high‐apogee (17.9 RE), inclined (40°), and elliptical orbit of European Space Agency's XMM‐Newton mission frequently passes through the Earth's Van Allen radiation belts on closed magnetospheric magnetic field lines, the magnetotail lobes on open magnetic field lines, and into the magnetosheath and solar wind on open solar magnetic field lines, four regions with very different energetic proton environments. We use XMM‐Newton measurements from 2000 to 2010 to survey the occurrence of proton strikes or "soft proton flares" on the European Photon Imaging Camera pn‐junction CCD detector. Proton flares affect ∼55% of all measurements. Rates vary from 50%at large radial distances in the solar wind and magnetosheath to 25% in the high‐latitude magnetotail lobes and increase to 66%of the measurements on closed low‐latitude magnetospheric magnetic field lines.